ANALISIS LOYALITAS KONSUMEN DALAM MENGKONSUMSI PRODUK PEMUTIH WAJAH (Studi Kasus pada Mahasiswa Fakultas Ekonomi UNISRI Surakarta) - Lamidi - (Universitas Slamet Riyadi, 2021)
ABSTRACT This research is aimed to find the influence of the dimensions skin whitening product, which consist of quality, public image, and advertising toward customer loyality, which measured through the intention to repurchase with same brand in the future. Through purposive sampling method, using samples 100 respondent were taken from student in area of economics faculty in UNISRI Surakarta. Logistic regression analysis with binary scaled-dependent variable is used to predict the influences dimensions skin whitening product which consist of of quality, public image, and advertising customer’s loyality. The result of the logistic regression analysis with binary scaled shows that there are three dimension of skin whitening product have the most significant effect in creating customer’s loyality through the intention to repurchase with same brand in the future The result of Exp(B) test shows that contribution which given by quality variable toward in creating customer’s loyality are bigger than another variables. Keywords: logistic binary regression, quality, public image, and advertising customer’s loyality, intention to repurchase with same brand in the future